AIR ACCESSIBILITY IN NORTHERN CANADA: PROSPECTS AND LESSONS FOR REMOTER COMMUNITIES - Alda Metrass Mendes; Richard de Neufville; Álvaro Costa (European Regional Science Association (ERSA), 2011)
This paper assesses the impact of Canada's air transportation policy on air accessibility of remote and arctic communities in a context of liberalization of the aviation industry. The central objective is to examine policy's impact on essential air service - travel and shipment. An observational study of the federal government's National Airports Policy (NAP) of divesting smaller airports to local entities is conducted using airport cases both inside and outside the National Airports System (NAS) covering 12 communities in Ontario (Ont.), Manitoba (Man.), British Columbia (B.C.), Quebec (Que.), the Northwestern Territories (NWT), and Yukon Territory (YT). The paper also evaluates the impact of Airports Operations and Maintenance Subsidy Program (O&MSP) and investigates the impact of several federal government departments in assuring air accessibility to remote areas. It is argued that: (a) local management allows for greater entrepreneurship and leads to some efficiency gains, (b) remote and arctic airports seem to be unable to sustain and operate their infrastructures without receiving local or federal contributions, and (c) Health Canada, Indian and Northern Affairs Canada (INAC), and Inuit organizations, such as the Makivik Corporation through its subsidiaries carriers First Air and Air Inuit, play a significant role in making air travel accessible. It concludes that, although the decentralization strategy and the subsidy mechanisms are benefiting remote communities, Canada's policy success is constrained by its failure to incorporate changing conditions, loss of focus, and flaws in performance evaluation.
Keywords: 330; National Airports Policy (NAP); Remote airports; Arctic airports; Inuit organizations; Health Canada; Indian and Northern Affairs Canada (INAC); Canada